Improving Quran Recitation: The Impact Of An Intensive Program For Non-Resident Students At MTs Unggulan Al-Qodiri - Napisa, Ainun; Rosidi, Ahmad; Sinta, Dewi (Al-Ulum: Jurnal Pendidikan Islam, 2025)
Reforms in the teaching and learning of the Qur'an can enhance the quality of religious education and spirituality within Islamic-based educational institutions. This study employs a descriptive qualitative research method to obtain a deeper understanding of the learning process. The findings reveal that the intensive Qur'anic program significantly improves the recitation quality of students at MTs Unggulan Al-Qodiri 1 Jember.